New teleomorphic and anamorphic taxa of Asterinaceous black mildew from Western coast of India - Natekar, Pratik D.; Patil, Anjali P.; Patil, Chandrahas R.; Bhise, Mahendra R.; Kambhar, Sidanand V. (Phytotaxa, 2024)
Asterinaceous black mildews are ectophytic, obligate biotrophs that live on many flowering plants, shrubs, and trees. Five new species were found in forests in the south western part of Maharashtra state. Two of these species produce sexual spores and are described in the genus Asterina. Two asexually reproducing species are described in Asterostomella and a third species in Asterostomula. All species are illustrated by photographs and line drawings.